Reliance Industries launches Mission COVID Infra - Reliance Industries Limited (2022)
In response to the sudden surge in COVID-19 cases, Reliance Foundation rapidly scaled scales up its COVID-19 operations to create 2,000+ bed facilities dedicated to COVID-19 care, making this the largest contribution by a philanthropic organisation to COVID-19 care across several locations of India.